Wahyu dah kurang: journalism practice among journalists in Malaysian mainstream media agencies during Pakatan Harapan tenure / Zafira Syamim Anwar and Nuurrianti Jalli - Anwar, Zafira Syamim; Jalli, Nuurrianti (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2020)
The change of government after the election upset in the Malaysian General Election 2018 placed the former government-affiliated media in a tricky situation. The conflict of interest in serving the Pakatan Harapan coalition as their government while UMNO was still their biggest shareholder has put some of the mainstream media agencies in Malaysia in an awkward situation. The change of government in 2018 promised a freer press by the returning prime minister Tun Dr Mahathir Mohamad, the same premier who approved a major media crackdown called Ops Lalang in 1987 that led to the detainment of many journalists and editors at that time, limiting press freedom. Ever since then, the spectre of Ops Lalang still lives in media houses curbing journalism practice among media practitioners to self-censor their writings. For this study, in-depth interviews were conducted with journalists of mainstream media from Utusan Malaysia, Kosmo, Berita Harian, Harian Metro, and New Straits Times to understand if the change of government had impacted their journalism practice. Findings revealed that while they may have more freedom to write news from a neutral perspective ever since the new government took over, journalists feel that they were mandated to serve the government of the day.